Perspectives of patients with metastatic breast cancer on physical exercise programs: results from a survey in five European countries - Sweegers, Maike; Depenbusch, Johanna; Kampshoff, Caroline S.; Aaronson, Neil K.; Hiensch, Anouk; Wengström, Yvonne; Backman, Malin; Gunasekara, Nadira; Clauss, Dorothea; Pelaez, Mireia; Lachowicz, Milena; May, Anne M.; et al. (Supportive care in cancer, 2023)
To successfully implement exercise programs for patients with metastatic breast cancer (MBC), services and patient education should consider patients’ knowledge, preferences, values, and goals. Hence, gaining insight into their perspectives on exercise and exercise programming is important.